The influence of personality, alexithymia and work engagement on burnout among village doctors in China: a cross-sectional study - Xuewen Zhang; Xue Bai; Liyan Bian; Min Wang (BMC, 2021)
Abstract Background In China, as the "gatekeepers"of rural residents' health, the primary-level village doctors, play a very crucial role in ensuring and serving the health level of rural residents. However, the burnout of village doctors is gravely threatening the stability of rural primary medical system step by step. This study systematically evaluated the effects of personality, work engagement and alexithymia on burnout of village doctors, and further measured and assessed the mediating effect of alexithymia and work engagement in the association between personality and burnout. Methods The subjects were 2684 village doctors in Jining, Shandong Province, China, from May to June 2019. Sociodemographic characteristics, alexithymia, personality, work engagement and job burnout were quantitated by self-completed questionnaire and measured by Likert 5-7 scale. One-way ANOVA, Person correlation analysis, and Structural Equation Modelling (SEM) were used for statistical analysis and mediating effect evaluation. Results 2693 questionnaires were collected in total, of which 2684 were valid, with an effective rate of 96.2%. 65.2% of village doctors were diagnosed with burnout, and 54.3% showed moderate to severe emotional exhaustion, 61.6% showed moderate to severe low sense of personal achievement, and 33.9% showed moderate to severe depersonalization burnout. Personality had a direct positive effect on work engagement (β = 0.50, p < 0.001), a direct negative effect on alexithymia (β = − 0.52, p < 0.001) and burnout (β = − 0.50, p < 0.001) respectively. Work engagement had a direct negative effect on burnout (β = − 0.10, p < 0.001), while alexithymia had a direct positive effect on burnout (β = 0.16, p < 0.001). In the path between personality and burnout, both work engagement 95%CI:(− 0.17)-(− 0.08), and alexithymia 95%CI:(− 0.36)-(− 0.09), have significant mediating effects. These results strongly confirm that personality, alexithymia, and work engagement are early and powerful predicators of burnout. Conclusion According to the results, medical administrators should pay attention to the personality characteristics of village doctors in vocational training, practice selection and job assignment, encourage village doctors to reflect on their own personality actively, and to reduce job burnout by obtaining necessary social support, constructing reasonable achievable career expectations, improving time management ability, and participating in psychological counselling programs.